Avaliação físico-química e microbiológica de tucupis comercializados em supermercados da cidade de Belém-Pa - LIMA, Moises Felipe Teixeira (2023)
Introduction. Tucupi is one of the main foods of Pará gastronomy, and its presence is more and more marked in Brazil, intensifying the sanitary surveillance control over this type of product. Goals. This labor aimed to carry out the physical-chemical and microbiological characterization of tucupi sold in a supermarket in Belém-Pará. Material and methods. The analyzes were performed at the Laboratory of Food Hygiene and Bioprocesses at the Federal University of Pará. Seven samples of tucupi were used, obtained from supermarket chains in Belém-Pa. For the physical-chemical analysis, the following were analyzed: pH, Brix, and total titratable acidity, free cyanide content and for the microbiological analysis: aerobic mesophiles, total and thermotolerant coliforms, molds, and yeasts. Results and discussion. Results ranged from 2.0 to 4.52 for pH, 1.0 to 8.0 for oBrix, and 6.6 to 16.0 meq NaOH.100 mL–1 for total titratable acidity. Free cyanide values ranged from 3.89 to 4.87 among the seven brands. The results for microbiological analysis ranged from 1.1x104 to 5.9x106 CFU/ml for molds and yeasts, from 1.2x105 to 1.3x108 CFU/ml for aerobic mesophiles and were absent for total coliforms and thermotolerant coliforms in all samples used. The highest count of molds and yeasts was observed for Tucupi VII, and the highest count of aerobic mesophiles was observed for Tucupi III. Conclusion. It was verified that, in general, the tucupi analyzed were within the contamination limits suggested by the legislation as suitable for consumption.